D-Enantiomeric Peptides that Eradicate Wild-Type and Multidrug-Resistant Biofilms and Protect against Lethal Pseudomonas aeruginosa Infections. Issue 2 (19th February 2015) - de la Fuente-Núñez, César; Reffuveille, Fany; Mansour, Sarah C.; Reckseidler-Zenteno, Shauna L.; Hernández, Diego; Brackman, Gilles; Coenye, Tom; Hancock, Robert E.W.
Summary: In many infections, bacteria form surface-associated communities known as biofilms that are substantially more resistant to antibiotics than their planktonic counterparts. Based on the design features of active antibiofilm peptides, we made a series of related 12-amino acid L-, D- and retro-inverso derivatives. Specific D-enantiomeric peptides were the most potent at inhibiting biofilm development and eradicating preformed biofilms of seven species of wild-type and multiply antibiotic-resistant Gram-negative pathogens. Moreover, these peptides showed strong synergy with conventional antibiotics, reducing the antibiotic concentrations required for complete biofilm inhibition by up to 64-fold. As shown previously for 1018, these D-amino acid peptides targeted the intracellular stringent response signal (p)ppGpp. The most potent peptides DJK-5 and DJK-6 protected invertebrates from lethal Pseudomonas aeruginosa infections and were considerably more active than a previously described L-amino acid peptide 1018. Thus, the protease-resistant peptides produced here were more effective both in vitro and in vivo. Graphical Abstract: Highlights: Identified novel D-enantiomeric peptides with potent antibiofilm activity These peptides conferred protection in two different invertebrate infection models Peptides demonstrated synergistic interactions with conventional antibiotics D-Enantiomeric peptides acted by preventing the accumulation of (p)ppGpp Abstract : Biofilms are associated with 65% of all bacterial infections in humans, and no drugs are licensed to target them. de la Fuente-Núñez et al. describe a class of antibiotics that eradicate biofilms in vitro and protect two nonvertebrate models against lethal P. aeruginosa infections.